Historical Reconstruction of Storm Surge Activity in the Southeastern Coastal Area of China for the Past 60 Years - Tao Ji; Guosheng Li; Rui Liu (Earth and Space Science, 2020)
Abstract It is a very difficult task to analyze the spatial and temporal variability of storm surge activity with current monitoring methods, because tide gauge observation, satellite altimeter, and numerical simulation do not ensure sufficient spatial and temporal resolution and temporal coverage at the same time. We propose to use a reanalysis data set, which covers the period from 1958 to 2016, to statistically reconstruct the daily maximum storm surge levels in the southeastern coastal area of China. Then, we used the Geographical Differential Analysis (GDA) calibration to correct the reconstruction results. The verification of the statistical model and the calibration results show that both the statistical model and the GDA calibration have a good accuracy in terms of high correlations and small errors. However, they also reveal a variable spatial quality of the multivariate statistical model in the reconstructed maximum storm surge levels, especially in the extreme events of the storm surge activity, the daily maximum surge is often underestimated. The GDA calibration result readily solves this problem, as it can accurately reflect not only the daily maximum storm surge levels but also the whole spatial and temporal dynamic storm surge evolution process. Therefore, this work provides an effective method to establish long‐term sequence and high‐precision daily maximum storm surge levels. This method can reveal the spatial and temporal evolution features of storm surge intensity at a climatic scale and main variability features. Moreover, it can predict possible trends in the geospatial distribution pattern of storm surge intensity in the context of future climate change.